Exploring The Effect of Wordtune Digital Writing Assistant: An Artificial Intelligence Tool focus on Students’ Academic Writing Skill - Muhammad Fadli; Iin Wahyudi; Ahmad, Dian Resty (Eduvelop: Journal of English Education and Development, 2024)
Abstract: wordtune is one of digital writing assistants generated by AI tools which can be accessed online. This study aimed to find out the effect of wordtune on students’ academic writing. This study was experimental research with quasi-experimental as the research design. There were 60 participants from a private university in South east Sulawesi, Indonesia. They were involved and selected purposively as the sample of the study. They then were grouped into two groups namely experimental and control group. Each of the groups consisted of 30 participants who receiving different treatments. The data were collected from writing tests and questionnaire. Thus, the participants on both groups doing the pretest and posttest, and filling out the questionnaire in the end of the study. The finding revealed that wordtune digital writing gave significant effect on students’ academic writing (Sig.00) or p<.005. Another finding showed that the students support the use of wordtune as the features namely paraphrase/rewrite, formal, shorten and expand help them to improve their performance on academic writing specifically on the aspects of general textual patterns, sentence construction and lexical choices. This study suggests the lecturers can employ wordtune in teaching academic writing to learners. In addition, this study also advices for further research to conduct a study in order to get more comprehensive result on wordtune and academic writing.